Air pollution, metabolites and respiratory health across the life-course. (10th August 2022) - Gruzieva, Olena; Jeong, Ayoung; He, Shizhen; Yu, Zhebin; de Bont, Jeroen; Pinho, Maria G.M.; Eze, Ikenna C.; Kress, Sara; Wheelock, Craig E.; Peters, Annette; Vlaanderen, Jelle; de Hoogh, Kees; et al.
Previous studies have explored the relationships of air pollution and metabolic profiles with lung function. However, the metabolites linking air pollution and lung function and the associated mechanisms have not been reviewed from a life-course perspective. Here, we provide a narrative review summarising recent evidence on the associations of metabolic profiles with air pollution exposure and lung function in children and adults. Twenty-six studies identified through a systematic PubMed search were included with 10 studies analysing air pollution-related metabolic profiles and 16 studies analysing lung function-related metabolic profiles. A wide range of metabolites were associated with short- and long-term exposure, partly overlapping with those linked to lung function in the general population and with respiratory diseases such as asthma and COPD. The existing studies show that metabolomics offers the potential to identify biomarkers linked to both environmental exposures and respiratory outcomes, but many studies suffer from small sample sizes, cross-sectional designs, a preponderance on adult lung function, heterogeneity in exposure assessment, lack of confounding control and omics integration. The ongoing EXposome Powered tools for healthy living in urbAN Settings (EXPANSE) project aims to address some of these shortcomings by combining biospecimens from large European cohorts and harmonised air pollution exposure and exposome data. Metabolomics offers the potential to identify biomarkers linked to both environmental exposures and respiratory health. Studies with prospectively collected biosamples and harmonised exposure assessment are needed for insights into mechanisms and causality. https://bit.ly/3MRF2iq